Painting the town cityscapes of New York ; paintings from the Museum of the City of New York (Yale Univ. Press, 2000)
Drawn from the collection of the Museum of the City of New York, these urban scene paintings reflect the shifting moods, restless energy and harsh contradictions of the metropolis.